No Injuries in European Sea Bass Tetanized by Pulse Stimulation Used in Electrotrawling. (29th March 2018) - Soetaert, M.; Verschueren, B.; Decostere, A.; Saunders, J.; Polet, H.; Chiers, K.
Abstract: Electrotrawling using electric pulse stimulation is a promising alternative to beam trawling in the brown shrimp Crangon crangon and Dover Sole Solea solea (also known as Solea vulgaris ) fisheries of the North Sea. In the sole fishery, a 40–80‐Hz pulse stimulation induces tetany in the muscles, which may result in injuries. Whereas no injuries have been reported in flatfish or selachian sharks and rays, electrically induced spinal injuries have been observed in gadoids such as Atlantic Cod Gadus morhua and Whiting (also known as European Whiting) Merlangius merlangus . This may indicate that fish species with a fusiform shape are more susceptible to electric pulses. Similar variation among species in electrically induced spinal injuries has been observed in freshwater electrofishing, although large variability in vulnerability has been reported among different freshwater fusiform species. Therefore, we aimed to assess the vulnerability of another, nongadoid, fusiform osteichthyan: Sea Bass Dicentrarchus labrax (also known as European Bass Morone labrax ). Two length groups of Sea Bass (31.3 ± 2.2 and 42.1 ± 2.5 cm) were exposed to electric pulses as used in commercial electrotrawls targeting Sole (80 bipolar pulses per second, 2% duty cycle). Thereafter, the fish were monitored daily and then euthanized 14 d after exposure for gross, radiographic, and histologic examination. No injuries were found in fish exposed to the electrical pulses. Differences in vertebral morphology among fusiform species may result in varying vulnerabilities to electrically induced spinal injuries. As a result, electrically induced spinal injuries and/or their variability in both marine and freshwater species may be determined by similar morphological parameters.